Whether ESG Performance is Conducive to Enhancing the Sustainable Development Ability of Enterprises - Based on the Analysis of State-owned Enterprises in China - Li, Sijie (Transactions on Economics, Business and Management Research, 2024)
With the increasingly prominent challenges of global climate change, the concept of a low-carbon economy has emerged. As the main participants in economic activities, the environmental, social, and corporate governance (ESG) performance of enterprises has gradually become an important indicator for measuring their sustainable development capabilities. As an important pillar of the national economy, China's state-owned enterprises not only bear economic responsibilities, but also shoulder social and political responsibilities, and their business behavior and policy orientation have a far-reaching impact on economic and social development. This paper focuses on Chinese state-owned enterprises, a special group of enterprises that occupies a core position in China's economic system and aims to explore whether ESG performance is conducive to enhancing the sustainable development ability of Chinese state-owned enterprises. Through an in-depth analysis of state-owned enterprises in China, this paper assesses the role of ESG factors in enhancing long-term competitiveness, promoting social responsibility, and enhancing corporate governance. The study found that enterprises with excellent ESG performance perform well in environmental protection, social responsibility fulfillment, and corporate governance structure optimization on a theoretical level. However, many enterprises still have some problems in ESG practice, which leads to a positive correlation between ESG performance and enterprise sustainability. This paper deeply explores the causes of these problems and proposes solutions. The research results of this paper provide practical guidance and theoretical support for state-owned enterprises to improve ESG performance and achieve sustainable development, and further provide a theoretical reference value for relevant policymakers.